If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 1 = y + -1 Reorder the terms: 1 + 2y = y + -1 Reorder the terms: 1 + 2y = -1 + y Solving 1 + 2y = -1 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 1 + 2y + -1y = -1 + y + -1y Combine like terms: 2y + -1y = 1y 1 + 1y = -1 + y + -1y Combine like terms: y + -1y = 0 1 + 1y = -1 + 0 1 + 1y = -1 Add '-1' to each side of the equation. 1 + -1 + 1y = -1 + -1 Combine like terms: 1 + -1 = 0 0 + 1y = -1 + -1 1y = -1 + -1 Combine like terms: -1 + -1 = -2 1y = -2 Divide each side by '1'. y = -2 Simplifying y = -2
| 0.768-b-0.4b=b+1.728 | | x^3-x^2-54x+144=0 | | .02x^2+0.1x-2=0 | | 5x+5-3x=14+3 | | 1.8r+9=-57r-6 | | 16x-9y=-5 | | 5x-24=x+36 | | 2x-5+3x=-4+4x+2 | | .02x^2+.5x-4=0 | | 16t^2+48t+64=0 | | 5x-8=76-7x | | 0.81-0.1v=2.6v-2.4v | | 10=.04v^2+1.1v | | -2(3r-9)-4(r-6)-13r= | | 3x+x+16=62 | | 2=7+w | | .04x^2+1.1x-2=0 | | 0.2w-0.15=0.875-0.4 | | 1/2(4x+2)=4x+8 | | 75=-5(-3-4x) | | 4k-40=-8 | | -2=3x | | 6(z-2)+4=10 | | 3(3x-5)-7x=25 | | -2(m-40)=-6m | | -2(x-1)17=12 | | x^2+2x-28=0 | | 8(7+y)=-24 | | -2(x-1)-17=12 | | 16-8y=4 | | 8(m+5)=-2+8m | | -6x+12=2(3x-6) |